A manufacturing process for strengthening the thermal shock resistance of special ceramic products
By constructing an integrated ceramic composite material, the differences in mechanical properties and thermal conductivity of ceramics and polyether ether ketones are used to solve the brittleness and heat conductivity problems of ceramic products in impact and high temperature environments, and their thermal shock resistance and thermal insulation properties are significantly improved.
Patent Information
- Application Number
- CN202411935527.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Ceramic products are highly brittle when impacted by external forces, easily cracks proliferate and breakage, and have fast heat conduction speed and low thermal insulation efficiency in high temperature environments.
By preparing alumina ceramic sheets and polyether ether ketone organic polymer sheets, an integrated ceramic composite material is constructed by alternating superposition, and a temperature gradient is formed through gradient heating to improve the thermal shock resistance of the material.
Through interface deflection, bifurcation and barrier mechanisms, energy is absorbed and crack propagation is reduced, which significantly improves the impact resistance of ceramic products; at the same time, the low thermal conductivity of polyether ether ketone hinders heat transfer and improves thermal insulation efficiency.
Smart Images

Figure CN119738310A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic products, in particular to a manufacturing process for strengthening the thermal shock resistance of special ceramic products. Background Art
[0002] Special ceramics refer to ceramics with special mechanical, physical or chemical properties, which are used in various modern industries and cutting-edge science and technology. The raw materials used and the required production process technology are quite different from those of ordinary ceramics. Special ceramics can be subdivided into structural ceramics, functional ceramics and tool ceramics according to their performance characteristics and uses.
[0003] The crystal structure and chemical bond characteristics of ceramic materials determine that they have high brittleness. When subjected to external impact, there is a lack of effective dislocation movement inside the ceramic to absorb energy, and cracks tend to expand rapidly, causing the ceramic product to break. For this reason, we propose a manufacturing process for strengthening the thermal shock resistance of special ceramic products. Summary of the invention
[0004] The purpose of the present invention is to provide a manufacturing process for strengthening the thermal shock resistance of special ceramic products.
[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solutions: a manufacturing process for strengthening the thermal shock resistance of special ceramic products, including preparing ceramic slices and performing performance testing on the ceramic slices. The specific operating steps of the manufacturing process for strengthening the thermal shock resistance of special ceramic products are as follows:
[0006] Step 1: using alumina powder to prepare alumina ceramic sheets;
[0007] Step 2, preparing a polyetheretherketone organic polymer sheet by extrusion molding;
[0008] Step 3, modifying the surfaces of the ceramic sheet and the polyetheretherketone organic polymer sheet by active gas plasma;
[0009] Step 4: constructing an integrated ceramic composite material by alternately stacking ceramic sheets and polyetheretherketone organic polymer sheets;
[0010] Step 5: construct a gradient heating device to make the integrated ceramic composite material sample experience a continuous temperature change from high temperature to low temperature to form a temperature gradient, and perform performance testing on the integrated ceramic composite material sample.
[0011] As a further scheme of the present invention: in the step 1, alumina powder, polyvinyl alcohol adhesive, dibutyl phthalate plasticizer and triolein dispersant are added to a stirrer, the amount of polyvinyl alcohol added is 3%-15% of the amount of alumina powder, the amount of dibutyl phthalate added is 20%-60% of the amount of polyvinyl alcohol, and the amount of triolein added is 0.5%-3% of the amount of alumina powder. The mixture is initially mixed by stirring at a rate of 300r / min-500r / min for 30min-60min, the initially mixed slurry is added to a ball mill for grinding and mixing, and the mixture is crushed at a ball mill speed of 100r / min-300r / min for 12h-48h. Zirconia balls are selected as ball milling media, and the ball-to-material ratio is set to 2-5:1. The ground slurry is added to a vacuum degasser for degassing, and the degassing is performed for 10min-30min at a vacuum degree of -0.08MPa--0.1MPa.
[0012] As a further scheme of the present invention: in the step 1, the defoamed slurry is poured into the hopper of the casting machine, polytetrafluoroethylene is selected as the material of the base film, the distance between the scraper and the base is set to 0.1mm-1mm, and when the casting machine is started, the slurry passes through the scraper at a speed of 1cm / min-10cm / min and is coated on the base film, the cast embryo film and the base are placed in a drying oven, dried at a temperature of 40℃-80℃ for 5h-10h, and after drying, the embryo film is removed from the base to obtain a raw embryo of the ceramic membrane, the raw embryo is placed in a muffle furnace, and the temperature is increased to 400℃-600℃ at a rate of 1℃ / min-5℃ / min and kept warm for 1h-5h, and after the insulation is completed, the temperature is increased to 1400℃-1600℃ at a rate of 5℃ / min-10℃ / min, and the ceramic sheet is obtained after sintering for 2h-6h.
[0013] As a further scheme of the present invention: in the step 2, polyetheretherketone particles with a purity of 99% are selected, the polyetheretherketone particles are added to a twin-screw extruder, and zinc stearate lubricant and antioxidant 1010 are added, the amount of zinc stearate added is 0.2%-0.5% of the amount of polyetheretherketone, the amount of antioxidant 1010 added is 0.2%-0.5% of the amount of polyetheretherketone, the temperature from the feeding section to the die of the twin-screw extruder is set to 350℃-360℃, 360℃-370℃, 370℃-380℃ and 380℃-390℃ respectively, the screw speed is set to 20r / min-60r / min and the traction speed is controlled at 2m / min-8m / min, the hot-melt polyetheretherketone is squeezed into a slit mold, the slit width is set to 0.5mm-0.6mm, and polyetheretherketone flakes are obtained by extrusion.
[0014] As a further solution of the present invention: In step 3, a radio frequency plasma device is used to perform surface treatment on the ceramic sheet, oxygen plasma is selected as the working gas, and the oxygen flow rate is set to 10m 3 / cm-50m 3 / cm, the power is set to 100W-300W, and the treatment time is set to 5min-10min. Before the plasma treatment for 2min-5min, the active gas ions collide with the grease and dust on the surface of the ceramic slice to clean the surface of the ceramic slice. When the treatment time reaches 5min-10min, the oxygen plasma reacts with the free radicals on the surface of the ceramic slice to introduce hydroxyl and carboxyl oxygen-containing functional groups on the surface of the ceramic slice.
[0015] As a further solution of the present invention: In the step 3, a radio frequency plasma device is used to perform surface treatment on the polyetheretherketone sheet, and nitrogen plasma is selected as the working gas, and the nitrogen flow rate is set to 5m 3 / cm-30m 3 / cm, the power is set to 150W-400W, the processing time is set to 1min-8min, and the high-energy ions in the argon plasma bombard the surface of the polyetheretherketone sheet. While etching the surface, the active gas in the nitrogen plasma will introduce amino nitrogen-containing functional groups on the surface of the polyetheretherketone sheet.
[0016] As a further solution of the present invention: in the step 4, the ceramic sheets and the polyetheretherketone sheets are alternately arranged one layer on top of another, the stacked material combination is placed in a hot pressing mold, and the vacuum degree of the hot pressing mold is drawn to 10 by a vacuum pump. -3 Pa-10 -4 Pa, and hot press the material combination at a temperature of 350°C-400°C and a pressure of 10MPa-30MPa for 1h-3h to form an integrated ceramic composite material.
[0017] As a further solution of the present invention: in the step five, the integrated ceramic composite material sample is a flat plate with a length of 300 mm, a width of 100 mm, and a thickness of 5 mm-10 mm. The inner wall length of the heating box is designed to be 400 mm, the width is 150 mm, and the height is 200 mm. In the length direction, the heating element is divided into three areas, starting from the high temperature end. The first area is 100 mm long and 5 silicon molybdenum rods are arranged, and the center spacing between two adjacent rods is 20 mm. The second area is 150 mm long and 4 rods are arranged with a spacing of 30 mm. The third area is 150 mm long and 3 rods are arranged with a spacing of 40 mm, so that the heating power forms a temperature gradient. The distance between the heating element and the integrated ceramic composite material sample is maintained at 10 mm-20 mm, and the number of thermal cycles is set to 100-500 times.
[0018] As a further solution of the present invention: in the step five, after completing the predetermined number of thermal cycles, the integrated ceramic composite material sample is taken out, and an optical microscope is used to observe the microstructural changes of the integrated ceramic composite material sample, including the distribution of cracks, interface debonding and grain growth. Hardness tests, tensile tests and bending tests are used to evaluate the changes in the mechanical properties of the integrated ceramic composite material sample, including hardness, strength and toughness. The phase composition and chemical composition changes of the integrated ceramic composite material sample are analyzed using X-ray diffraction methods.
[0019] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0020] 1. The present invention constructs an integrated ceramic composite material by alternately stacking ceramic sheets and organic polymer sheets. When the integrated ceramic composite material is subjected to external force, cracks encounter the interface between the ceramic sheets and the polyetheretherketone sheets during the expansion process. Since the elastic modulus and mechanical properties of ceramics and polyetheretherketone are very different, the cracks will deflect, bifurcate, or even be blocked by the interface. This huge difference causes the cracks to change direction when encountering the interface, thereby consuming a large amount of energy and preventing the cracks from expanding rapidly. The organic polymer sheets can also act as a buffer layer. When impacted, the organic polymer can absorb energy through its own deformation, reduce stress concentration, avoid sudden fracture of the material, and make the composite material show better impact resistance.
[0021] 2. The thermal conductivity of the organic polymer sheet of the present invention is relatively low. The thermal conductivity of polyetheretherketone is about 0.25W / (m·K), while the thermal conductivity of ceramic materials is generally higher at about 25W / (m·K). When they are alternately superimposed, the polyetheretherketone sheet hinders the rapid transfer of heat inside the material to a certain extent, and plays a role in heat insulation. In the heat insulation components used in high temperature environment, this structure can effectively reduce the heat conduction speed and improve the heat insulation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure is a schematic diagram of the manufacturing process for enhancing the thermal shock resistance of special ceramic products in an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0024] The present invention provides a special ceramic product thermal shock resistance enhancement manufacturing process, including preparing ceramic slices and testing the performance of the ceramic slices. The specific operation steps of the special ceramic product thermal shock resistance enhancement manufacturing process are as follows:
[0025] Step 1: using alumina powder to prepare alumina ceramic sheets;
[0026] Step 2, preparing a polyetheretherketone organic polymer sheet by extrusion molding;
[0027] Step 3, modifying the surfaces of the ceramic sheet and the polyetheretherketone organic polymer sheet by active gas plasma;
[0028] Step 4: constructing an integrated ceramic composite material by alternately stacking ceramic sheets and polyetheretherketone organic polymer sheets;
[0029] Step 5: construct a gradient heating device to make the integrated ceramic composite material sample experience a continuous temperature change from high temperature to low temperature to form a temperature gradient, and perform performance testing on the integrated ceramic composite material sample.
[0030] In one embodiment of the present invention: in step one, alumina powder, polyvinyl alcohol adhesive, dibutyl phthalate plasticizer and triolein dispersant are added to a stirrer, the amount of polyvinyl alcohol added is 3%-15% of the amount of alumina powder, the amount of dibutyl phthalate added is 20%-60% of the amount of polyvinyl alcohol, and the amount of triolein added is 0.5%-3% of the amount of alumina powder. The mixture is initially mixed at a rate of 300r / min-500r / min for 30min-60min, and the initially mixed slurry is added to a ball mill for grinding and mixing. The mixture is crushed at a ball mill speed of 100r / min-300r / min for 12h-48h, zirconium oxide balls are selected as ball milling media, and the ball-to-material ratio is set to 2-5:1. The ground slurry is added to a vacuum degasser for degassing, and the degassing is performed for 10min-30min at a vacuum degree of -0.08MPa--0.1MPa.
[0031] In one embodiment of the present invention: in step one, the defoamed slurry is poured into the hopper of a casting machine, polytetrafluoroethylene is selected as the material of the base film, the distance between the scraper and the base is set to 0.1mm-1mm, and when the casting machine is started, the slurry passes through the scraper at a speed of 1cm / min-10cm / min and is coated on the base film, the cast embryo film and the base are placed in a drying oven, and dried at a temperature of 40℃-80℃ for 5h-10h. After drying, the embryo film is removed from the base to obtain a raw embryo of the ceramic membrane, and the raw embryo is placed in a muffle furnace, and the temperature is increased to 400℃-600℃ at a rate of 1℃ / min-5℃ / min and kept warm for 1h-5h. After the insulation is completed, the temperature is increased to 1400℃-1600℃ at a rate of 5℃ / min-10℃ / min, and the ceramic sheet is obtained after sintering for 2h-6h.
[0032] In one embodiment of the present invention: in step 2, polyetheretherketone particles with a purity of 99% are selected, the polyetheretherketone particles are added to a twin-screw extruder, and zinc stearate lubricant and antioxidant 1010 are added, the amount of zinc stearate added is 0.2%-0.5% of the amount of polyetheretherketone, the amount of antioxidant 1010 added is 0.2%-0.5% of the amount of polyetheretherketone, the temperature from the feeding section to the die of the twin-screw extruder is set to 350℃-360℃, 360℃-370℃, 370℃-380℃ and 380℃-390℃ respectively, the screw speed is set to 20r / min-60r / min and the traction speed is controlled at 2m / min-8m / min, the hot-melt polyetheretherketone is squeezed into a slit mold, the slit width is set to 0.5mm-0.6mm, and polyetheretherketone flakes are obtained by extrusion.
[0033] In one embodiment of the present invention: In step 3, a radio frequency plasma device is used to perform surface treatment on the ceramic sheet, oxygen plasma is selected as the working gas, and the oxygen flow rate is set to 10m 3 / cm-50m 3 / cm, the power is set to 100W-300W, and the treatment time is set to 5min-10min. Before the plasma treatment for 2min-5min, the active gas ions collide with the grease and dust on the surface of the ceramic slice to clean the surface of the ceramic slice. When the treatment time reaches 5min-10min, the oxygen plasma reacts with the free radicals on the surface of the ceramic slice to introduce hydroxyl and carboxyl oxygen-containing functional groups on the surface of the ceramic slice.
[0034] In one embodiment of the present invention: In step 3, a radio frequency plasma device is used to perform surface treatment on the polyetheretherketone sheet, and nitrogen plasma is selected as the working gas, and the nitrogen flow rate is set to 5m 3 / cm-30m 3 / cm, the power is set to 150W-400W, the processing time is set to 1min-8min, and the high-energy ions in the argon plasma bombard the surface of the polyetheretherketone sheet. While etching the surface, the active gas in the nitrogen plasma will introduce amino nitrogen-containing functional groups on the surface of the polyetheretherketone sheet.
[0035] In one embodiment of the present invention, in step 4, ceramic sheets and polyetheretherketone sheets are alternately arranged one layer on top of another, the stacked material combination is placed in a hot pressing mold, and a vacuum pump is used to draw the vacuum degree of the hot pressing mold to 10 -3 Pa-10 -4 Pa, and hot press the material combination at a temperature of 350°C-400°C and a pressure of 10MPa-30MPa for 1h-3h to form an integrated ceramic composite material.
[0036] In one embodiment of the present invention: in step five, the integrated ceramic composite material sample is a flat plate with a length of 300mm, a width of 100mm, and a thickness of 5mm-10mm. The inner wall length of the heating box is designed to be 400mm, the width is 150mm, and the height is 200mm. In the length direction, the heating element is divided into three areas, starting from the high temperature end. The first area is 100mm long and 5 silicon molybdenum rods are arranged, and the center spacing between two adjacent rods is 20mm. The second area is 150mm long and 4 rods are arranged with a spacing of 30mm. The third area is 150mm long and 3 rods are arranged with a spacing of 40mm, so that the heating power forms a temperature gradient. The distance between the heating element and the integrated ceramic composite material sample is maintained at 10mm-20mm, and the number of thermal cycles is set to 100-500 times.
[0037] In one embodiment of the present invention: in step five, after completing a predetermined number of thermal cycles, the integrated ceramic composite material sample is taken out, and an optical microscope is used to observe the microstructural changes of the integrated ceramic composite material sample, including the distribution of cracks, interface debonding and grain growth. Hardness tests, tensile tests, and bending tests are used to evaluate the changes in the mechanical properties of the integrated ceramic composite material sample, including hardness, strength and toughness. The phase composition and chemical composition changes of the integrated ceramic composite material sample are analyzed using X-ray diffraction methods.
[0038] Example 1: Ceramic powder, binder, plasticizer and dispersant were added to the solvent in a certain proportion, and a mechanical stirrer was used for preliminary stirring at a stirring speed of 500 r / min for 50 min to make the components uniformly mixed.
[0039] Ball milling: The slurry after preliminary mixing is transferred to a ball mill for ball milling. Ball milling can make the ceramic powder more evenly dispersed in the solvent and additives, and can also further refine the powder particles. The ball milling time is 24h, the ball milling speed is 200r / min, the ball milling medium is zirconia balls, and the ball-to-material ratio is 2:1-5:1;
[0040] Vacuum degassing: The slurry after ball milling contains bubbles, which will affect the quality of the green body. The slurry is placed in a vacuum degassing device for degassing. The vacuum degree is -0.1MPa and the degassing time is 30min, until there are no obvious bubbles in the slurry.
[0041] Tape casting: adjust the scraper of the tape casting machine to a suitable height. The gap between the scraper and the base tape determines the thickness of the ceramic film. The gap between the scraper and the base tape is set to 0.5mm. Select a polytetrafluoroethylene-based tape film. The base tape thickness is usually 50um. Pour the defoamed slurry into the hopper of the tape casting machine, start the tape casting machine, and allow the slurry to pass through the scraper at a uniform speed and be coated on the base tape. The casting speed is 5cm / min. During the tape casting process, ensure that the slurry supply is stable to avoid uneven thickness.
[0042] Drying treatment: Put the cast green film together with the base tape into a drying oven for drying. The drying temperature is controlled at 60°C and the drying time is 5 hours. The blast drying method is adopted. During blast drying, the wind speed is 2m / s, which helps to speed up the drying speed and make the drying more uniform.
[0043] Green film peeling: The adhesion between the green film and the base tape will decrease after drying. Carefully peel the green film from the base tape to obtain the green ceramic film.
[0044] Debinding treatment: Before sintering, the green body needs to be debinded to remove organic additives in the body. The green body is placed in a muffle furnace and heated to 500°C at a heating rate of 3°C / min and kept at this temperature for 3 hours to fully decompose and volatilize the organic matter.
[0045] High temperature sintering: The green body after debinding is sintered at high temperature to cause a solid phase reaction between the ceramic powder particles to form a dense ceramic material. The sintering temperature is 1500℃, the heating rate is generally 8℃ / min, and the holding time is 5h to obtain ceramic sheets.
[0046] Embodiment 2: At the beginning of plasma treatment, active gas ions collide with grease and dust on the surface of ceramic sheets, decompose and remove them, and achieve surface cleaning. At the same time, high-energy particles in the plasma bombard the ceramic surface, break the surface chemical bonds, generate free radicals, and activate the surface. The oxygen ions in the plasma react with the carbon impurities on the surface to generate carbon dioxide and be removed. At the same time, the Al-O bonds on the surface of alumina are broken to generate Al and O free radicals. As the treatment time increases, the active gas molecules react with the free radicals on the surface of the ceramic sheets to introduce specific functional groups, and oxygen-containing functional groups such as hydroxyl (-OH) and carboxyl (-COOH) are introduced on the ceramic surface. These functional groups can significantly improve the hydrophilicity of the surface of the ceramic sheets, making it easier to bond with polyetheretherketone.
[0047] Example 3: For polyetheretherketone sheets, plasma treatment will first produce a surface etching effect. The high-energy ions in the argon plasma bombard the surface of polyetheretherketone, breaking the CC bonds and CO bonds in its molecular chain, removing the surface material, thereby increasing the surface roughness. Scanning electron microscope observation found that the surface of polyetheretherketone was relatively smooth before treatment, and after treatment, obvious microscopic grooves and protrusions appeared, and the roughness could be increased from less than 1μm to several microns. While etching the surface, the active gas in the plasma will also introduce active groups on the surface of the polyetheretherketone sheet. For example, nitrogen plasma can introduce amino nitrogen-containing functional groups on the surface of polyetheretherketone. The introduction of these functional groups changes the surface chemical properties of polyetheretherketone, increases its surface energy, and changes it from the original low surface energy and hydrophobic state to a state with certain hydrophilicity and chemical reactivity.
[0048] As attached Figure 1 As shown, alternately stacked ceramic sheets and polyetheretherketone sheets are pressed into an integrated ceramic composite material by hot pressing, thereby improving the thermal shock resistance and impact resistance of ceramic products.
[0049] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
[0050] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0051] The above contents are merely examples and explanations of the present invention. Various modifications or additions to the specific embodiments described or replacements in similar ways by technicians in the technical field shall fall within the protection scope of the present invention as long as they do not deviate from the invention or exceed the scope defined by the claims.
[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A manufacturing process for strengthening the thermal shock resistance of special ceramic products, comprising preparing ceramic slices and testing the performance of the ceramic slices, characterized in that: The specific operation steps of the special ceramic product thermal shock resistance enhancement manufacturing are as follows: Step 1: using alumina powder to prepare alumina ceramic sheets; Step 2, preparing a polyetheretherketone organic polymer sheet by extrusion molding; Step 3, modifying the surfaces of the ceramic sheet and the polyetheretherketone organic polymer sheet by active gas plasma; Step 4: constructing an integrated ceramic composite material by alternately stacking ceramic sheets and polyetheretherketone organic polymer sheets; Step 5: construct a gradient heating device to make the integrated ceramic composite material sample experience a continuous temperature change from high temperature to low temperature to form a temperature gradient, and perform performance testing on the integrated ceramic composite material sample.
2. The manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 1 is characterized in that: In the step 1, alumina powder, polyvinyl alcohol adhesive, dibutyl phthalate plasticizer and triolein dispersant are added to a stirrer, wherein the amount of polyvinyl alcohol added is 3%-15% of the amount of alumina powder, the amount of dibutyl phthalate added is 20%-60% of the amount of polyvinyl alcohol used, and the amount of triolein added is 0.5%-3% of the amount of alumina powder used. The mixture is initially mixed at a rate of 300 r / min-500 r / min for 30 min-60 min, and the initially mixed slurry is added to a ball mill for grinding and mixing. The mixture is crushed at a ball mill speed of 100 r / min-300 r / min for 12 h-48 h, zirconium oxide balls are selected as ball milling media, and the ball-to-material ratio is set to 2-5:
1. The ground slurry is added to a vacuum degasser for degassing, and the degassing is performed for 10 min-30 min at a vacuum degree of -0.08 MPa--0.1 MPa.
3. The thermal shock resistance enhancement manufacturing process of special ceramic products according to claim 2 is characterized in that: In the step 1, the defoamed slurry is poured into the hopper of the casting machine, polytetrafluoroethylene is selected as the material of the base film, the distance between the scraper and the base is set to 0.1mm-1mm, and when the casting machine is started, the slurry passes through the scraper at a speed of 1cm / min-10cm / min and is coated on the base film, the cast embryo film and the base are placed in a drying oven, and dried at a temperature of 40°C-80°C for 5h-10h, and after drying, the embryo film is removed from the base to obtain a raw embryo of the ceramic membrane, and the raw embryo is placed in a muffle furnace, and the temperature is increased to 400°C-600°C at a rate of 1°C / min-5°C / min and kept warm for 1h-5h, and after the insulation is completed, the temperature is increased to 1400°C-1600°C at a rate of 5°C / min-10°C / min, and the ceramic sheet is obtained after sintering for 2h-6h.
4. The manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 1 is characterized in that: In the step 2, polyetheretherketone particles with a purity of 99% are selected, the polyetheretherketone particles are added to a twin-screw extruder, and zinc stearate lubricant and antioxidant 1010 are added, the amount of zinc stearate added is 0.2%-0.5% of the amount of polyetheretherketone, the amount of antioxidant 1010 added is 0.2%-0.5% of the amount of polyetheretherketone, the temperature from the feeding section to the die of the twin-screw extruder is set to 350°C-360°C, 360°C-370°C, 370°C-380°C and 380°C-390°C, the speed of the screw is set to 20r / min-60r / min and the traction speed is controlled at 2m / min-8m / min, the hot-melt polyetheretherketone is squeezed into a slit die, the slit width is set to 0.5mm-0.6mm, and the polyetheretherketone sheet is extruded.
5. The manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 3 is characterized in that: In step 3, the ceramic sheet is surface treated using radio frequency plasma equipment, oxygen plasma is selected as the working gas, and the oxygen flow rate is set to 10m 3 / cm-50m 3 / cm, the power is set to 100W-300W, and the treatment time is set to 5min-10min. Before the plasma treatment for 2min-5min, the active gas ions collide with the grease and dust on the surface of the ceramic slice to clean the surface of the ceramic slice. When the treatment time reaches 5min-10min, the oxygen plasma reacts with the free radicals on the surface of the ceramic slice to introduce hydroxyl and carboxyl oxygen-containing functional groups on the surface of the ceramic slice.
6. The manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 4 is characterized in that: In step 3, a radio frequency plasma device is used to treat the surface of the polyetheretherketone sheet, and nitrogen plasma is selected as the working gas, and the nitrogen flow rate is set to 5m 3 / cm-30m 3 / cm, the power is set to 150W-400W, the processing time is set to 1min-8min, and the high-energy ions in the argon plasma bombard the surface of the polyetheretherketone sheet. While etching the surface, the active gas in the nitrogen plasma will introduce amino nitrogen-containing functional groups on the surface of the polyetheretherketone sheet.
7. A manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 6, characterized in that: In the fourth step, the ceramic sheets and the polyetheretherketone sheets are alternately stacked one layer at a time, the stacked material combination is placed in a hot pressing mold, and the vacuum degree of the hot pressing mold is evacuated to 10 -3 Pa-10 -4 Pa, and hot press the material combination at a temperature of 350°C-400°C and a pressure of 10MPa-30MPa for 1h-3h to form an integrated ceramic composite material.
8. The manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 7 is characterized in that: In the step five, the integrated ceramic composite material sample is a flat plate with a length of 300 mm, a width of 100 mm, and a thickness of 5 mm-10 mm. The inner wall length of the heating box is designed to be 400 mm, the width is 150 mm, and the height is 200 mm. In the length direction, the heating element is divided into three areas, starting from the high temperature end. The first area is 100 mm long and 5 silicon molybdenum rods are arranged. The center spacing between two adjacent rods is 20 mm. The second area is 150 mm long and 4 rods are arranged with a spacing of 30 mm. The third area is 150 mm long and 3 rods are arranged with a spacing of 40 mm. The heating power forms a temperature gradient. The distance between the heating element and the integrated ceramic composite material sample is maintained at 10 mm-20 mm, and the number of thermal cycles is set to 100-500 times.
9. A manufacturing process for strengthening the thermal shock resistance of special ceramic products according to claim 8, characterized in that: In the step five, after completing the predetermined number of thermal cycles, the integrated ceramic composite material sample is taken out, and an optical microscope is used to observe the microstructural changes of the integrated ceramic composite material sample, including the distribution of cracks, interface debonding and grain growth. Hardness tests, tensile tests, and bending tests are used to evaluate the changes in the mechanical properties of the integrated ceramic composite material sample, including hardness, strength and toughness. The phase composition and chemical composition changes of the integrated ceramic composite material sample are analyzed using an X-ray diffraction method.